Liquation and post-weld heat treatment cracking in Rene 80 laser repair welds - Rush, Matthew T.; Colegrove, Paul A.; Zhang, Zhu; Broad, David (Elsevier, 2012)
An extensive experimental study on a nickel-based superalloy, Rene 80 using autogenous laser welding has been undertaken to determine the effect of the process parameters and weld bead geometry on cracking in the as-welded and post- weld heat treated conditions. Little cracking was observed in the as-welded condition with low powers and beam diameters around 2.5mm. Welding speed had little effect on the incidence of cracking in the as-welded condition. Investigation of the aspect ratio (penetration divided by width) indicated that little cracking occurred in the as-welded condition when the aspect ratio was approximately 0.5. The same effect was observed with the post-weld heat treated samples. An analysis of the microstructures indicated that the cracking was caused primarily by liquation in the as-welded condition and was exacerbated by post-weld heat treatment cracking during the subsequent heat treatment. Finally the study resolved some of the contradictory findings in the literature on the effect of process parameters on the incidence of cracking in the as-welded and post-weld heat treated conditions.
Keywords: Liquation cracking; Nickel superalloy; Laser welding; Strain-age cracking; Post weld heat treatment cracking; Rene 80; Repair welding; PWHT cracking